Late Miocene mammals from the Calchaquí Valley (Palo Pintado formation, northwestern Argentina) : biogeographic and paleoenvironmental implications for the southern central Andes - Candela, Adriana Magdalena (2021)
Fil: Candela, Adriana Magdalena. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.